Dance anthropology and the impact of 1930s Haiti on Katherine Dunham's scientific and artistic consciousness - Durkin, Hannah (Intellect Journals, 2011)
Katherine Dunham (1909-2006) was one of the most critically and commercially successful dancers of the twentieth century. She established and ran the Katherine Dunham Dance Company, the earliest self-supporting predominantly black dance company and one of the first modern dance troupes to achieve international success. She was also one of the first African Americans to conduct anthropological fieldwork, and the first anthropologist to explore the function of dance in rituals and community life. Her observations of dance rituals whilst working as a graduate researcher in 1930s Haiti played a formative role in her dance. Her choreographic method combined Caribbean cultural forms with ballet and modern dance practices and has had a profound but rarely acknowledged influence on twentieth century dance. This article examines Dunham's anthropological memoir, Island Possessed (1969), to explore the formative role that Haiti played on Dunham's scientific and artistic consciousness. It contends that Island Possessed articulates a highly reflexive engagement with ethnography, re-envisaging anthropological research as a space of intercultural exchange. It shows how the text sheds light on a lifelong project by Dunham to enact an artistic and cultural legitimization of Haiti by incorporating its ritual dance forms onto the concert dance stage, an endeavour that would ensure a significant Haitian influence over North American dance throughout the mid-twentieth century.